The Oxford handbook of sports history - Wilson, Wayne; Edelman, Robert 1945- (New York, NY Oxford University Press, 2017)
The Oxford handbook of sports history provides a comprehensive and rigorous survey of this field's burgeoning body of scholarship, proving that sports are not only the opposite of war but have also been a significant part of a historical civilizing process
Part I. Theorizing sport history -- Part II. Premodern sport -- Part III. The birth and establishment of modern sport, 1820-1940 -- Part IV. Patterns of diffusion -- Part V. Sites of sport development -- Part VI. New globalizations and their discontents -- Part VII. Reconsidering established categories and contemplating new ones -- Part VIII. Emerging area of interest
Includes bibliographical references and index.
Keywords: Sports -- History; Sports -- Social aspects